Ekstrak Daun Erpa (Aerva sanguinolenta) sebagai Pewarna Alami pada Kain Batik - Febrian Ardi Pramuditya; Ayu Jamilatulhumairah Noor; Tutik Muji Setyaningrum; Siswanti Siswanti (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
Until now, the use of natural dyes for coloring textiles continues to increase, so the search for natural dye sources need to be improved. Erpa leaf (Aerva sanguinolenta) contain natural dyes that have the potential to be used as a textile dye. This study aims to determine the optimum extraction conditions Erpa leaves and calculate the mass transfer coefficient will then be applied and tested on the fabric. The parameters studied were extraction temperature, the ratio of leaf with a solvent, application and test on the fabric. extraction is done at 30oC, 40oC, 50oC, 60oC and 70oC. Variations in the use of leaf Erpa was 5, 10, 15, 20 and 25 grams with 350 ml of solvent. The results showed the optimum conditions for the extraction of leaves Erpa at 70 ° C with a ratio of weight and volume 25 g / 350 ml of ethanol with the mass transfer coefficient obtained 25,29 x10- 3 l / min. The effect of sunlight on the durability of the color gets the number 2 and the leaching effect on the durability of the colors got number 3.